The adjunctive role of metformin in patients with mild to moderate ulcerative colitis: a randomized controlled study - Binsaleh, Ammena Y.; El-Haggar, Sahar M.; Hegazy, Sahar K.; Maher, Maha M.; Bahgat, Monir M.; Elmasry, Thanaa A.; Alrubia, Sarah; Alsegiani, Amsha S.; Eldesoqui, Mamdouh; Bahaa, Mostafa M. (Frontiers in Pharmacology, 2025)
BackgroundMetformin, hypoglycemic medication, is recognized for its diverse properties and its capacity to influence the inflammatory pathways. Medications with anti-inflammatory and anti-oxidative characteristics have been demonstrated to be able to elicit and sustain remission in ulcerative colitis (UC), chronic inflammatory disorder of the bowel. Studies in both preclinical and clinical settings have looked into the several metabolic pathways via which metformin protects against UC.AimTo assess efficacy of metformin as adjunctive therapy in patients with mild to moderate UC.MethodsThis clinical research was double-blinded, randomized, controlled, and involved 60 patients with mild to moderate UC. The participants were randomly assigned to one of two groups (n = 30). The control group was given 1 g of mesalamine three times a day (t.i.d.) for a period of 6 months (mesalamine group). The metformin group was given 500 mg of metformin twice daily and 1 g of mesalamine t. i.d. For a period of 6 months. Patients with UC were assessed by a gastroenterologist using the disease activity index (DAI) both at the beginning of treatment and 6 months thereafter. To evaluate the drug’s biological efficacy, measurements of fecal calprotectin, serum C-reactive protein (CRP), interleukin 10 (IL-10), and nitric oxide (NO) were taken both before and after treatment.Study outcomesDecrease in DAI and change in the level of measured serum and fecal markers.ResultsThe metformin group displayed a statistical reduction in DAI (p = 0.0001), serum CRP (p = 0.019), NO (p = 0.04), and fecal calprotectin (p = 0.027), as well as a significant increase in IL-10 (p = 0.04) when compared to the mesalamine group. There was a significant direct correlation between DAI and calprotectin (p < 0.0001, r = 0.551), and between DAI and CRP (p < 0.0001, r = 0.794). There was a significant negative correlation between DAI and IL-10 (p = 0.0003, r = 0.371).ConclusionMetformin may be an effective adjunct drug in management of patients with mild to moderate UC by decreasing DAI and other inflammatory markers that were involved in the pathogenesis of UC.Clinical Trial Registrationidentifier NCT05553704.